Environment and society: a relationship to be thought from life - Battestin, Cláudia; Nogaro, Arnaldo; Cerutti, Elisabete (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article presents a theoretical essay on Environmental Education whose emphasis occurs from an ontological principle that aims to life. As literature, the study is of reflections that refer to beware of all forms of life, establishing the relationship of man with nature, a place where there is the centrality of environmental education. Although there contextualization that human exploration changed the natural balance, the test think strategies and solutions to overcome the environmental crisis. As the conclusion, the Belgrade Charter while promoting individual to the construction of citizenship from the Environmental Education and human responsibility.